PF-7 Pre Slaughter Stunning of Ruminant Slaughter Based on MUI HAS 23103 2012, MS 1500 2009 and SNI 99003 2018 - . Supratikno; Danang Dwi Cahyadi; Heru Setijanto (Hemera Zoa, 2018)
The debate about the use of pre slaughter stunning (PSS) in halal slaughter is still an interesting topic to discuss due to the difficulties to determine the stunned animal are unconscious or dead. Indonesia and Malaysia as a country with majority Muslim population have recognized non-penetrative PSS (NPPSS) as a method in halal slaughter. Indonesian Council of Ulama (MUI) issued the Halal Assurance System (HAS 23103 2012)[1] as guidelines for animal slaughter process, while Department of Standard Malaysia issued Malaysian Standard (MS) 1500 2009[2], which regulate Halal Food-Production, preparation Handling and Storage-General Guidelines. Recently, the Indonesian National Standardization Body issued Indonesia's National Standard for ruminant halal slaughter (SNI 99003 2018) [3]. This article will discuss mechanical NPPSS based on these three guidelines in animal welfare and halal perspective